Approaches to Styrenyl Building Blocks for the Synthesis of Polyene Xanthomonadin and its Analogues. Issue 38 (7th October 2018) - Madden, Katrina S.; Laroche, Benjamin; David, Sylvain; Batsanov, Andrei S.; Thompson, Daniel; Knowles, Jonathan P.; Whiting, Andrew
Abstract : A number of aryl building blocks for the synthesis of two xanthomonadin natural product pigments, as well as a related analogue, were accessed using a divergent hydroboration/bromoboration approach from a key alkynyl intermediate. A new approach towards substitution patterns around the ring was adopted following the isolation of an unexpected regioisomer from the bromination reaction. Potential coupling reactions onto these building blocks were explored, with a successful Sonogashira coupling performed on the key alkynyl intermediate, and with the key debrominated styrenyl boronate ester intermediate functionalised both by preliminary Suzuki–Miyaura coupling and by iododeboronation/Heck–Mizoroki coupling. Coupling reactions with brominated styrenyl intermediates proved much more challenging due to the instability of the intermediates to cross‐coupling, but some studies have shown promise. Abstract : Several polyenyl pigments related to Xanthomonadin are known to be produced by some plant‐based bacteria, acting as inhibitors of UV‐mediated oxidative stress. This paper discusses these unusual, little known and long polyenes, and lays out a strategy to construct these unstable systems.